Comparative Study of Children and Adolescents Referred for Eating Disorder Treatment at a Specialist Tertiary Setting - Walker, T.; Watson, Hunna; Leach, D.; McCormack, J.; Tobias, K.; Hamilton, M.; Forbes, D. (John Wiley & Sons, Inc., 2014)
To examine child and adolescent differences in the clinical presentation of eating disorders (EDs) at referral to a specialist pediatric program